The Causes of Populism in the West - Berman, Sheri (Annual Review of Political Science, 2021)
The global ascendance of populism has produced an explosion of research, bringing together scholarship on American and comparative politics as well as encouraging intellectual exchange among political scientists, economists, and sociologists. A good way to get a handle on what is now a wide-ranging and interdisciplinary literature is to focus on the key debates characterizing it. This article reviews the literature on the causes of populism, and in particular right-wing populism, in the United States, Europe, and other advanced industrial nations generally, but much of this literature draws on and refers to research on other parts of the world as well. This review analyzes the nature as well as the strengths and weakness of demand- and supply-side explanations of populism, economic grievance–based and sociocultural grievance–based explanations of populism, and structure- and agency-based explanations of populism.
Keywords: right-wing radicalism